Efficient RhB degradation and antimicrobial activity with molecular docking study of polymers doped ZnSe nanostructure - Irshad, Ahmad; Ikram, Muhammad; Haider, Ali; Shahzadi, Anum; Ul-Hamid, Anwar; Ullah, Hameed [UNESP]; Nisar, Muhammad; Ayari-Akkari, Amel (Elsevier, 2024)
A facile coprecipitation approach was adopted to synthesize zinc selenide (ZnSe) doped with a fixed amount (3 wt%) of cetyltrimethylammonium bromide (CTAB) and different concentrations (2 and 4 wt%) of eudragit to form ternary nanostructure (NSs). Eud and CTAB inhibit the dimension and reduce the rate of recombination of NSs to intensify catalytic performance against rhodamine B (RhB) and bactericidal action against MDR Staphylococcus aureus (S. aureus). Doped ZnSe increase active sites, porosity, and surface area to enhance the degradation of RhB dye and antimicrobial efficacy to kill pathogenic S. aureus. Assessment of 4 wt% Eud/CTAB exhibited effective performance for degradation of RhB and bactericidal potential highlights an impressive 94.3 % degradation efficiency and 8.85 ± 0.05 mm of the inhibition zone against MDR S. aureus. Computational molecular docking studies suggest that NSs, such as Eud/CTAB-doped ZnSe, have the ability to inhibit the DNA gyrase enzyme in MDR S. aureus.
Keywords: Antimicrobial; Catalytic degradation; Eudragit; Molecular docking; Zinc selenide